Finger millet blast pathogen diversity and management in East Africa: a summary of project activities and outputs - Takan, J.P.; Akello, B.; Esele, P.; Manyasa, E.O.; Obilana, A.B.; Audi, P.O.; Kibuka, J.; Odendo, M.; Oduori, C.A.; Ajanga, S.; Bandyopadhyay, Ranajit; Muthumeenakshi, S.; et al. (2004)
Sorghum Improvement Conference of North America, Lubbock, USA, International Sorghum and Millets Newsletter 45:66-69. This paper covers the results of studies on the genetic diversity of Magnaporthe grisea causing blast disease in finger millet (Eleusine coracana) in East Africa; pathogen aggressiveness and epidemiology; disease and socioeconomic surveys in Kenya; and finger millet varietal screening for blast resistance.